Gestión de Riesgo Operativo en la Cooperativa de Ahorro y Crédito CACEC Ltda. - Álvarez Veintimilla, Elsa Paulina (2022)
The current study has been developed with the purpose of contributing to the savings and credit cooperative CACEC in the diagnosis of operational risk, since the stability and continuity of this institution in the market depends on its control and surveillance, which is exposed towards various risk factors, both internal and external. Under a mixed approach, after having analyzed the theoretical framework on which this application is based, we proceeded to adapt the instruments provided by the Superintendence of Popular and Solidarity Economy to measure the Operational Risk, Basel II Law and COSO II ERM, and through a Likert scale that focused on five evaluation parameters: "Totally agree", "agree", "undecided", "disagree", "totally disagree" it was possible to acquire the level at which it is implemented operational risk management in the entity. Using the obtained results, and through a correlation analysis and a "non-parametric" hypothesis test, it was possible to establish the effect of the analysis variables on the cooperative's profitability. On the other hand, the operational risk was specifically evaluated, applying the same instrument to different departments, whose results were reflected in the heat maps, allowing the organization's activities with the greatest shortcomings to be identified based on the frequency-severity relationship that the group put together. to risk factors such as: human resources, technology, processes, external events, among others, that directly impact the Cooperative and business continuity.